2011
DOI: 10.1002/adv.20262
|View full text |Cite
|
Sign up to set email alerts
|

Nonisocyanate polyurethane/silica hybrid coatings via a sol–gel route

Abstract: Polyurethane/silica hybrids by a nonisocyanate route were prepared by reacting cyclic carbonate-modified bis(4-glycidyloxy phenyl)phenyl phosphine oxide (BGPPO), and poly(propyleneglycol)diglycidyl ether (PPG-DGE) with hexamethylene diamine. The incorporation of silica was achieved via a sol-gel method. The effect of silica and phosphine oxide moiety on polyurethane coating properties was studied by physical, mechanical, and thermal tests. Modulus and hardness of the coatings were enhanced by increasing the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The sol-gel method has been widely used as an alternative technology in preparing monoliths, powders, coatings and fibers [1][2][3][4]. In recent years, there has been significant interest in preparing continuous inorganic and organic-inorganic hybrid fibers using sol-gel method [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel method has been widely used as an alternative technology in preparing monoliths, powders, coatings and fibers [1][2][3][4]. In recent years, there has been significant interest in preparing continuous inorganic and organic-inorganic hybrid fibers using sol-gel method [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal properties of the compounds were evaluated with a DSC Model Q20 (TA Instruments). The measurements were performed under an inert atmosphere of nitrogen between 285 and 200 C at a heating rate of 10 C min 21 . The heating cycle was performed twice to eliminate the thermal history of the sample.…”
Section: Characterization Of Pu-hybrid Silica Filmsmentioning
confidence: 99%
“…The addition of hybrid silicas to PU has also improved the thermal stability and increased the hydrophobicity . Hosgor et al reported an increase in flame retardancy, modulus and hardness for hybrid silica‐PU composites . Athawale and Kulkarni observed that the addition of silica precursors during the polymer synthesis generated stronger polymer‐silica interactions than those obtained when silica was added after the polymer synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also claimed that the hydroxyl groups formed by the aminolysis reactions between cyclic carbonates and amines activated the alkoxysilane hydrolytic condensation (the process of cross-linking). Such approach is indeed a good example of the synergic effect of hybrid materials.Hosgor et al prepared polyhydroxyurethane-silica hybrid coatings via sol-gel routes [144]. First two difunctional cyclic carbonates were obtained from bis(4-glycidyloxy phenyl)phenyl phosphine oxide and poly(propyleneglycol)diglycidyl ether.…”
mentioning
confidence: 99%